Advanced photovoltaic concepts for perovskite solar cells - Fong, Melvin Shao Feng (Nanyang Technological University, 2022)
The shortage of energy has always been an issue for the society. Many researchers have been diving into different aspects to discover new methods to obtain a clean and renewable energy. In the present day, a new type of solar cell which is made of the perovskite materials has become one of most popular type of photovoltaic (PV) device among researchers and scientists, due to its rapid growth of efficiency during the last 10 years [11]. Across the globe, there are various methods currently adopted to fabricate perovskite PV cells. In this paper, PCBM, PEDOT:PSS, as well as MAPbI3 are used as materials for the fabrication processes In this thesis, various methods would be discussed and spin coating process will be focused on. The paper continues with the analysis of the connection between the number of spins for the hole transport layer (HTL) and electron transport layer (ETL) deposition process, as well as the impact on the efficiency of the PV device.